1989
DOI: 10.1128/aem.55.2.412-418.1989
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ozone and Sulfur Dioxide on Phyllosphere Fungi from Three Tree Species

Abstract: Short-term effects of ozone (03) on phyllosphere fungi were studied by examining fungal populations from leaves of giant sequoia (Sequoiadendron giganteum (Lindl.) Buchholz) and California black oak (Quercus kelloggii Newb.). Chronic effects of both 03 and sulfur dioxide (SO2) were studied by isolating fungi from leaves of mature Valencia orange (Citrus sinensis L.) trees. In this chronic-exposure experiment, mature orange trees were fumigated in open-top chambers at the University of California, Riverside, fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1990
1990
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Marked reductions in the colony numbers of Cladosporium spp. in response to SO2 have been reported in Norway spruce {Picea abies (L.) Karsten) stands by Langkramer & Lettl (1982) and on attached leaves of Valencia orange {Citrus .sinensis L.) by Fenn, Dunn & Durall (1989). In addition, the level of Eusarium infection in tillers of winter wheat {Tritieum aestivum L.) has been found to be negatively correlated with SO2 treatment concentrations of up to 60 nmol moP ' (McLeod 1988),…”
Section: Discussionmentioning
confidence: 78%
“…Marked reductions in the colony numbers of Cladosporium spp. in response to SO2 have been reported in Norway spruce {Picea abies (L.) Karsten) stands by Langkramer & Lettl (1982) and on attached leaves of Valencia orange {Citrus .sinensis L.) by Fenn, Dunn & Durall (1989). In addition, the level of Eusarium infection in tillers of winter wheat {Tritieum aestivum L.) has been found to be negatively correlated with SO2 treatment concentrations of up to 60 nmol moP ' (McLeod 1988),…”
Section: Discussionmentioning
confidence: 78%
“…There have been no reports on microbial-mediated O 3 reduction. However, in a study of O 3 effects on phyllosphere fungal populations, Fenn et al ( 1989 ) found that a chronic exposure of mature Valencia orange trees ( Citrus sinensis ) to O 3 or SO 2 for 4 years decreased populations of phyllosphere fungi. In a same experiment conducted by the authors, a short-term fumigation of O 3 to giant sequoia ( Sequoiadendron giganteum ) and California black oak ( Quercus kelloggii ) did not significantly affect the numbers of phyllospere fungi.…”
Section: Roles Of Leaves and Phyllosphere Microbes In Air Remediationmentioning
confidence: 99%
“…This may be related to nutrient competition between different microbes and various degrees of sensitivity or resistance to haze pollution. Fenn et al [19] found that the diversity of phyllosphere fungi of giant cedar (Western Arborvitae) could be altered confronting ozone and sulfur dioxide. Artificial aerosol can markedly reduce the diversity of bacteria, filamentous fungi, and yeast in mango leaves [20].…”
Section: Discussionmentioning
confidence: 99%